Prevalence of restless legs syndrome and sleep problems in Korean children and adolescents with attention deficit hyperactivity disorder: a single institution study - Soonhak Kwon; Youngsoo Sohn; Seong-Hoon Jeong; Un-Sun Chung; Hyeeun Seo (Korean Pediatric Society, 2014)
PurposeAttention deficit hyperactivity disorder (ADHD) is a common disorder in school-aged children. Patients with restless legs syndrome (RLS) often present with ADHD symptoms and vice versa. This study was the first to attempt to identify the prevalence of RLS and sleep problems in children with ADHD in Korea.MethodsPatients diagnosed with ADHD were asked to complete a sleep questionnaire. The sleep questionnaire included items to help identify the presence of four typical symptoms that are used as diagnostic criteria for RLS.ResultsA total of 56 patients, including 51 boys and 5 girls (mean age, 10.7 years old) participated. Of these, 24 complained of pain, discomfort, or an unpleasant sensation in the legs. Based on the RLS diagnostic criteria, 2 patients were diagnosed with definite RLS and 4 with probable RLS. There were no significant differences in age, medication dosage, or neuropsychological test scores between the patients with and without RLS symptoms.ConclusionApproximately 42.9% of patients with ADHD presented with RLS symptoms and 7.1% of these were diagnosed with RLS. Patients with ADHD also experienced various other sleep disorders. Thus, appropriate assessment and treatment for sleep disorders in patients with ADHD is essential.